2002
DOI: 10.1034/j.1600-0714.2002.310403.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation activity and the expression of cell cycle regulatory proteins in oral lichen planus

Abstract: These complex changes, which concomitantly occur in the injured mucosal epithelium, could contribute to the development and maintenance of characteristic mucosal epithelial architectures seen in OLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
43
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 32 publications
6
43
1
6
Order By: Relevance
“…Due to ethical considerations and lack of normal tissue blocks the control group in the present study consisted of epithelial hyperplasia with no dysplasia. It is considerable that result of comparison between groups A and B in this study was similar to other studies in which OLP have been compared to normal mucosa regardless of the evaluation methods and cell proliferation markers applied (Tipoe et al, 1996;Hirota et al, 2002;Taniguchi et al, 2002;Lee et al, 2005;González Moles et al, 2009;HadziMihailovic et al, 2012). In contrast, Bloor et al (1999) reported no difference for Ki67 expression between the OLP and normal mucosa (Bloor et al, 1999).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Due to ethical considerations and lack of normal tissue blocks the control group in the present study consisted of epithelial hyperplasia with no dysplasia. It is considerable that result of comparison between groups A and B in this study was similar to other studies in which OLP have been compared to normal mucosa regardless of the evaluation methods and cell proliferation markers applied (Tipoe et al, 1996;Hirota et al, 2002;Taniguchi et al, 2002;Lee et al, 2005;González Moles et al, 2009;HadziMihailovic et al, 2012). In contrast, Bloor et al (1999) reported no difference for Ki67 expression between the OLP and normal mucosa (Bloor et al, 1999).…”
Section: Discussionsupporting
confidence: 85%
“…The injured cells in OLP target some complex molecular mechanisms in order to arrest cell cycle (to repair their damaged DNA and maintain genomic stability) or in order to activate apoptosis pathway (to eliminate cells with severity damaged DNA) (Hirota et al, 2002;Taniguchi et al, 2002;Bascones-Ilundain et al, 2008;Liu et al, 2010;Georgakopoulou et al, 2012). In addition, these injured cells can enter cell cycle and proliferate (Liu et al, 2010;Georgakopoulou et al, 2012) Although mechanisms involved in an increase in proliferation are still unknown (Hirota et al, 2002), one of the mechanisms might be related to the release of cytokines and inflammatory mediators from injured keratinocytes or inflammatory cells in OLP (da Silva Fonseca and do Carmo, 2001;Liu et al, 2010;Mattila et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, markers of cellcycle arrest, such as p27, may be expected to increase in the presence of these drugs (Malik et al, 2003). Apoptosis, which could also conceivably increase with certain interventions, is such a rare event in the normal buccal mucosa that its usefulness as a potential PD marker is uncertain (Hirota et al, 2002;Loro et al, 2002;Hague et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of normal tissue for a given drug study is likely to depend on a number of different factors, including the level and variability of expression of the biomarker of interest. Literature reports suggest that the buccal mucosa has a high baseline proliferation index (Jordan et al, 1998;Hirota et al, 2002;Kurokawa et al, 2003), making it a potentially attractive tissue for assessing antiproliferative end points. Unfortunately, these indices are often obtained from individuals undergoing follow up for various oral pathologies, therefore field effects skewing these 'normal' values cannot be ruled out.…”
mentioning
confidence: 99%